Justicia flava leaf extract potently relaxes pregnant human myometrial contractility: a lead plant for drug discovery of new tocolytic drugs. Issue 12 (2nd November 2020) - Bafor, Enitome E.; Prendergast, Clodagh; Wray, Susan
Abstract : New Findings: What is the central question of this study? Can Justicia flava leaf extract (JF) inhibit human myometrial contractility as was previously shown in mouse myometrium? What is the main finding and its importance? JF abolished human myometrial contractions and therefore presents as a lead plant in drug discovery studies involving drugs for preterm birth. Abstract: In the search for new potent therapies for preterm labour, Justicia flava leaf extract (JF) was previously shown to potently inhibit uterine contractility in both pregnant and non‐pregnant mouse uterus. This study took the investigation a step further and investigated the activity of JF on pregnant human myometrial contractility. JF potently inhibited human myometrial contractility in a concentration‐dependent manner. This pilot study provides evidence that JF should be further investigated as a lead plant in the drug discovery of new uterine relaxants. Abstract :